Revision of the Mexican subgenus Carabomimus Kolbe, 1895 (Coleoptera: Carabidae: Calosoma Weber, 1801): C. depressicolle, C. flohri and C. digueti species groups - Häckel, Martin; Heinz, Walter; Sehnal, Rostislav (Zootaxa, 2011)
It is revised the central Mexican species of the C. (Carabomimus) depressicolle species complex, included in the subgenus Carabomimus Kolbe, 1895, genus Calosoma Weber, 1801. The complex is divided into two species groups, depressicolle and flohri. A key to all species groups of the subgenus Carabomimus (depressicolle, digueti, flohri, politum and striatulum) inhabiting this area is included, whereas C. bulleri (Beheim & Breuning, 1943) was left unassigned. Another key to all five species of the complex (species groups depressicolle and flohri) is likewise included. It is described C. flohri zirostense ssp. n. (México: Michoacán), and the previously synonymized C. lesnei Breuning, 1931 and C. gebieni Breuning, 1931 are restablished as valid taxa. C. asper (Jeannel, 1940) is downgraded as subspecies of C. depressicolle Chaudoir, 1869, whereas C. altipeta (Jeannel, 1940) and C. sylvestre (Lassalle, 2009) are ranked as species. C. digueti colimaense (Lassalle 2009) is considered to be a subspecies of C. flohri.